What Can Affect Gen Y’s Purchase Intention of Halal Food in Indonesia? - Makhfudz, Akhmad Affandi; Febrian Prihandiansyah; Bin Lahuri, Setiawan; Muchammad Taufiq Affandi (LPPM ISNJ Bengkalis, 2025)
Abstract This study aims to analyze religiosity and the theory of planned behavior factors that influenced Gen Y’s purchase intention of Halal food in Indonesia. The mediating effect of attitude towards intention to purchase Halal food was also investigated. This research method employs the Structural Equation Modeling (SEM) method where the sampling technique is purposive sampling with 415 young Muslim millennials generations who live in Indonesia. Data were collected through disseminating questionnaires. This result of study is religiosity has no effect on the purchase intention of Halal food and the subjective norm has no effect on the purchase intention of Halal food in Indonesia. On the other side, the attitude affects the purchase intention of Halal food, and perceived behavior control affects Halal food purchase intention. Religiosity affects attitude. Religiosity affects the purchase intention of Halal food through attitude. Keywords: Religiosity, Purchase Intention, Halal Food, SEM